Terapi Perilaku Kognitif untuk Menurunkan Gejala Gangguan Neurotik pada Dewasa Muda - Rizki Maulana Hidayatullah; Finanin Nur Indana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing neurotic symptoms among young adults. Neurotic disorders, characterized by excessive anxiety, emotional instability, and psychosomatic complaints, often affect university students during transitional periods. Using a quasi-experimental pretest-posttest control group design, 30 participants were divided equally into an experimental group receiving six sessions of CBT and a control group receiving no treatment. Data were collected through a validated neurotic disorder scale and analyzed using paired and independent sample t-tests. Results revealed a significant decrease in neurotic symptoms in the experimental group after the intervention, while the control group showed no meaningful change. The findings support the use of CBT as an effective therapeutic approach for reducing neurotic symptoms through cognitive restructuring and adaptive behavioral training. This research highlights the relevance of culturally adapted CBT in university counseling settings and encourages the development of structured group programs to address mental health issues among young adults. Further studies are recommended to explore broader applications across diverse populations and institutional contexts.